Issues and developments in international trade policy - Kelly, Margaret... et. al (I.M.F. Washington, D.C.US, 1992)
Reviews major issues and developments during one period 1988-1991 and outlines the challenges governments face as they seek to liberalize trade in the Uruguay Round of trade negotiations and addresses 'new' trade issues.